Faktor Resiko Terjadinya Stunting Pada Balita Umur 12-24 Bulan - hamidah, siti (IJMT : Indonesian Journal of Midwifery Today, 2022)
Indonesia is one of the countries with toddler nutrition problems, namely triple double. One of the nutritional problems in Indonesia that is a major concern is the high number of stunted children under five. The purpose of the study was to determine the risk factors for stunting in toddlers aged 12-24 months. This type of research is observational with a cross sectional design. The sampling technique is by using the calculation of the slovin formula and random sampling technique. The sample of the study was some mothers who had toddlers aged 12-24 months in Karangpoh Village, Gresik District, Gresik Regency as many as 86 respondents. The study was conducted in January 2023 for 2 weeks. Its independent variables include frequency, quantity and variety of foods. The dependent variable is stunting toddlers aged 12-24 months. The instruments used are MCH books, microtois and checklists. The analysis used was univariate and bivariate using spearman rank correlation. The results showed that there was a relationship between the frequency of supplementary feeding (p = 0.008), there was a relationship between the number of supplementary feedings (p = 0.011) and there was a relationship between the type of supplementary feeding (p = 0.007) with the nutritional status of toddlers aged 12-24 months. The results of this study are expected to provide information and input on risk factors associated with the incidence of stunting in toddlers, especially toddlers aged 12-24 months, so that preventive efforts can be made to reduce the prevalence of stunting in toddlers aged 12-24 months. Indonesia termasuk salah satu negara dengan permasalahan gizi balita yaitu triple ganda. Salah satu masalah gizi di Indonesia yang menjadi perhatian utama adalah masih tingginya anak balita stunting. Tujuan penelitian yaitu mengetahui faktor resiko terjadinya stunting pada balita umur 12-24 bulan. Jenis penelitian adalah observational dengan desain cross sectional. Teknik pengambilan sampel yaitu dengan menggunakan perhitungan rumus slovin dan teknik random sampling. Sampel penelitian adalah sebagian ibu yang memiliki balita umur 12-24 bulan di Kelurahan Karangpoh Kecamatan Gresik Kabupaten Gresik sebanyak 86 responden. Penelitian dilaksanakan bulan Januari 2023 selama 2 minggu. Variabel bebasnya meliputi frekuensi, jumlah dan variasi makanan. Variabel terikatnya adalah balita stunting umur 12-24 bulan. Instrumen yang digunakan adalah buku KIA, microtois dan ceklist. Analisis yang digunakan adalah univariat dan bivariat menggunakan korelasi spearman rank. Hasil penelitian menunjukkan bahwa ada hubungan frekuensi pemberian makanan tambahan (p=0,008), ada hubungan jumlah pemberian makanan tambahan (p=0,011) dan ada hubungan jenis pemberian makanan tambahan (p=0,007) dengan status gizi balita umur 12-24 bulan. Hasil penelitian ini diharapkan dapat memberikan informasi dan masukan tentang faktor resiko yang berhubungan dengan kejadian stunting pada balita khususnya balita umur 12-24 bulan , sehingga dapat dilakukan upaya-upaya pencegahan untuk menurunkan prevaensi stunting balita umur 12-24 bulan.